ECOPROJECT TEMPAT SAMPAH BAMBU: MEDIA EDUKASI PENGELOLAAN SAMPAH UNTUK MENINGKATKAN KESADARAN LINGKUNGAN SISWA - Umar, Umar; Setiawan, Dedi; Sabri, Debi; Kartika, Dian (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
Solid waste management at the elementary school level remains a crucial issue due to low student awareness and a lack of adequate educational media. This study aimed to design and implement an eco-project in the form of bamboo waste bins as an educational medium for waste management to enhance students’ environmental awareness. Bamboo was chosen for its eco-friendly properties, easy availability, and familiarity in students’ daily lives. These attributes were expected to bridge the gap between the ideals of environmental education and real-world practices in schools. The study employed a Participatory Action Research (PAR) approach, involving teachers and students at every stage (planning, implementation, observation, and reflection). Evaluation instruments included interviews, observations, and documentation to assess student engagement and behavioral change. The project resulted in four functional bamboo waste bins installed at strategic points around the school. Field findings indicated positive support from teachers and students, improved discipline in proper waste disposal, and the emergence of collective awareness to maintain cleanliness. Teacher role modeling proved essential in strengthening social norms, while active student participation in maintaining the facilities fostered a shared sense of ownership. This eco-project was effective as both a contextual learning tool and a means of cultivating a culture of environmental care. The study contributes to environmental education literature by emphasizing the importance of integrating place-based education, experiential learning, and ecological citizenship. ABSTRAKPengelolaan sampah di tingkat sekolah dasar masih menjadi isu krusial karena rendahnya kesadaran siswa dan minimnya media edukatif yang memadai. Penelitian ini bertujuan untuk merancang dan menerapkan ecoproject berupa pembuatan tempat sampah dari bambu sebagai media edukasi pengelolaan sampah guna meningkatkan kesadaran lingkungan siswa. Bambu dipilih sebagai bahan karena ramah lingkungan, mudah diperoleh, dan akrab dengan keseharian siswa; dengan demikian diharapkan dapat menjembatani kesenjangan antara idealisme pendidikan lingkungan dan praktik nyata di sekolah. Penelitian ini menggunakan metode Participatory Action Research (PAR) dengan melibatkan guru dan siswa pada setiap tahap (perencanaan, pelaksanaan, observasi, dan refleksi). Instrumen evaluasi berupa wawancara, observasi, dan dokumentasi digunakan untuk menilai tingkat keterlibatan siswa serta perubahan perilaku. Ecoproject ini menghasilkan empat unit tempat sampah bambu fungsional yang ditempatkan di titik strategis sekolah. Hasil pengamatan menunjukkan dukungan positif dari guru dan siswa, peningkatan disiplin dalam membuang sampah pada tempatnya, dan tumbuhnya kesadaran kolektif menjaga kebersihan lingkungan. Keteladanan guru menjadi faktor penting yang memperkuat norma sosial, sedangkan partisipasi aktif siswa dalam merawat fasilitas memupuk rasa memiliki bersama. Ecoproject ini efektif sebagai media pembelajaran kontekstual sekaligus sarana membangun budaya peduli lingkungan. Studi ini berkontribusi pada literatur pendidikan lingkungan dengan menegaskan pentingnya integrasi konsep place-based education, experiential learning, dan ecological citizenship.